Autonomic Nervous System Function in Anorexia Nervosa: A Systematic Review - Jenkins, Zoe M.; Eikelis, Nina; Phillipou, Andrea; Castle, David J.; Wilding, Helen E.; Lambert, Elisabeth A. (Frontiers in Neuroscience, 2021)
Background Autonomic nervous system (ANS) dysfunction has been suggested to contribute to the high prevalence of cardiovascular complications in individuals with anorexia nervosa (AN), yet has not been thoroughly investigated. The current review aimed to synthesise the evidence of basal ANS function in individuals with a current diagnosis of AN and those with a previous diagnosis who had achieved weight restoration, as compared to controls. Methods A systematic review of nine databases was conducted and studies that were published in a peer-review journal, in English, that included at least one assessment of ANS function in individuals with a current or previous diagnosis of AN were selected. 46 studies were included with a total of 811 participants with a current diagnosis of AN and 123 participants with a previous diagnosis of AN. Results ANS function was assessed through heart rate variability (n=27), orthostatic challenge, blood pressure variability or baroreflex sensitivity (n=11), adrenergic activity (n=14), skin conductance level (n=4) and pupillometry (n=1). Individuals with AN demonstrated increased parasympathetic activity and decreased sympathetic activity, suggestive of autonomic dysregulation. Following weight restoration, autonomic function trended towards, or was equivalent to, control levels. Discussion Autonomic dysregulation is indicated through a range of assessments in individuals with AN. Future investigations should utilise a variety of assessments together in order to conclusively establish the nature of autonomic dysfunction in AN, and following extended weight restoration. Moreover, investigation into the co-occurrence of ANS function and cardiovascular risk is required.